Effect of dazoxiben, a specific inhibitor of thromboxane synthetase, on acute pulmonary responses to E. coli endotoxin in anaesthetized cats - Ball, H. A. (1983)
1 The effects of acute pretreatment with the thromboxane synthetase inhibitor dazoxiben 5 mg/kg intravenously (UK 37248-01) were examined on the acute pulmonary responses of pentobarbitone-anaesthetized cats to E. coli endotoxin 2 mg/kg intravenously. 2 E. coli endotoxin in control, untreated, cats resulted in a marked pulmonary hypertension, an increase in intra-tracheal pressure (at a constant pulmonary inflation volume), an increase in both pulmonary arterial and aortic concentrations of thromboxane B(2) (TXB(2)) and a reduction in systematic arterial PO(2). 3 Dazoxiben prevented, or markedly reduced, the endotoxin-induced pulmonary release of TXB(2), the decrease in systematic arterial PO(2) and the pulmonary arterial hypertension, but did not modify the increase in intratracheal pressure. 4 These results may suggest that TXA(2) is responsible for the endotoxin-induced pulmonary arterial hypertension but that some other arachidonic acid derivative (prostaglandin F(2α)) is responsible for the reduced lung compliance that follows the acute administration of E. coli endotoxin.